ANALISIS PERILAKU KONSUMEN PADA HARGA PRODUK TERHADAP MINAT BELI KONSUMEN - Rahmayani, Anita; Fasa, Muhamad Iqbal (STAI Darul Qalam Tangerang, 2024)
The current development of the business world with the implementation of free trade has the impact of increasingly tight business competition, this requires business actors to be more observant and sharper in seeing existing opportunities and observing the behavior of consumers who are their target market. The method used in this writing is qualitative which uses a descriptive approach. The aim of this research is to provide marketing solutions that are the spearhead of the marketing department which should know how consumer behavior relates to consumer buying interest which will be the key to success in marketing activities. For this reason, the author wishes to provide a brief review of the influence of consumer behavior on product prices. (Halim, 2021)